Educational differences in years lived with disability due to mental and substance use disorders: a cohort study using nationwide Norwegian and Danish registries - Nanna Oerslev Weye; Oleguer Plana-Ripoll; Carl Michael Baravelli; Emilie E. Agardh; Lode van der Velde; Jonas Minet Kinge; Ann Kristin Skrindo Knudsen (BMC, 2024)
Abstract Background Findings from the Global Burden of Disease (GBD) study have shown that the burden of mental and substance use disorders is considerable, and unevenly distributed across demographic groups in the population. However, there is a lack of knowledge on how this burden differs by socioeconomic position. The aim of this study was to examine educational differences in years lived with disability (YLDs) from mental and substance use disorders among males and females in two high-income countries, taking comorbidity with other diseases into account. Methods The study included all registered residents in Denmark and Norway from 2011 to 2021. Diagnostic information was retrieved from records in the Norwegian National Patient Registry (NPR) and the Danish Psychiatric Central Research Register (PCRR) and used as proxy measures for disorder prevalence. Demographical and educational information was taken from administrative registries. The YLD is a measure of the non-fatal health loss in the population and was calculated by multiplying the duration of a disorder with a disability weight (DW), scaled between 0 and 1. Information on remission and DWs were retrieved from the GBD study and other sources, and disorder specific DWs were averaged by severity levels and adjusted for comorbidity. Results Educational gradients in YLD rates were found for mental and substance disorders overall, and for most of the specific disorders. The educational gradient was more pronounced for schizophrenia, intellectual disability and substance use disorders than for eating, anxiety, and affective disorders. Both higher YLD rates, and a larger attributed proportion of the total YLDs, were found for schizophrenia, intellectual disability, and substance use disorders in the groups with low versus high education. YLD rates for eating, anxiety, and affective disorders were more equal across educational levels, but constituted a smaller proportion of the total YLDs among the groups with low versus the groups with high educational level. Conclusion Most of the disease burden related to mental and substance use disorders falls on those with the fewest years of education. This should be taken into consideration when public health targets aimed at improving mental health and reducing social inequalities in health are developed and implemented.